2020
DOI: 10.1080/10410236.2020.1847437
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Misinformation with Face Mask Wearing and Social Distancing in a Nationally Representative US Sample

Abstract: Widespread misinformation about the COVID-19 pandemic has presented challenges for communicating public health recommendations. Should campaigns to promote protective behaviors focus on debunking misinformation or targeting behavior-specific beliefs? To address this question, we examine whether belief in COVID-19 misinformation is directly associated with two behaviors (face mask wearing and social distancing), and whether behavior-specific beliefs can account for this association and better predict behavior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 29 publications
5
81
1
1
Order By: Relevance
“…For example, civic attitudes (Roma et al, 2020) and trust in science and scientists (Dohle et al, 2020;Hromatko et al, 2021) are found to be positively related to adherence to COVID-19 protective measures. However, while some previous research, consistent with this study, show that education is negatively related to beliefs in conspiracies (Hornik et al, 2021), some other show that education is not a significant predictor (Hromatko et al, 2021;Karić and Mededović, 2021) or is even negatively related to compliance to protective measures (Roma et al, 2020). These results suggest that the relationship of education with belief in conspiracies and adherence to protective measures is not straightforward.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, civic attitudes (Roma et al, 2020) and trust in science and scientists (Dohle et al, 2020;Hromatko et al, 2021) are found to be positively related to adherence to COVID-19 protective measures. However, while some previous research, consistent with this study, show that education is negatively related to beliefs in conspiracies (Hornik et al, 2021), some other show that education is not a significant predictor (Hromatko et al, 2021;Karić and Mededović, 2021) or is even negatively related to compliance to protective measures (Roma et al, 2020). These results suggest that the relationship of education with belief in conspiracies and adherence to protective measures is not straightforward.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, correlation with age was found in studies by Freeman et al (2020), Constantinou et al (2020), Earnshaw et al (2020), although the correlation differed in sample size. Regarding education, income, and religiosity, previous research demonstrated relationships in line with lower-income and education levels (Constantinou et al, 2020;Hornik et al, 2021) and a higher level of religiosity (Alper et al, 2020), which were related to a higher endorsement of COVID-19 conspiracy theories.…”
Section: Discussionmentioning
confidence: 92%
“…Related research has shown intentions to be associated with social distancing behavior and other preventive behaviors, including hand washing, respiratory hygiene, and staying at home [ 4 , 5 , 8 ]. Evidence suggests more frequent mask-wearing is positively associated with beliefs about related behavioral outcomes, need for cognition, self-control, risk aversion, and more liberal political orientation and negatively associated with beliefs in misinformation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the limited discussion on the persistent negative influence of misinformation, scholars (e.g., [ 7 , 23 , 25 , 26 , 27 ]) in the field of health and digital communication began to investigate individuals’ perceived impact of misleading information online. Liu and Huang [ 26 ], for instance, published their latest article about the third-person effects of fake news about COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When people face uncertainties due to this disease and continuously social distance, social media platforms provide a critical role in fulfilling diversified gratifications, such as information needs, social needs to connect with friends and families, and fun or enjoyment obtained from entertainment [ 4 , 5 ]. However, without prudent journalistic judgments of media content online, misinformation, referring to false and misleading information, began circulating rapidly on social media [ 6 , 7 ]. For instance, misinformation has made many people believe that using salt water or drinking bleach could kill the virus during the pandemic [ 8 ].…”
Section: Introductionmentioning
confidence: 99%